THE EFFECTIVENESS OF REGIONAL GOVERNMENT FINANCIAL PERFORMANCE - Dendi Purnama; Neni Nurhayati; Arum Sekaraji (JASS (Journal of Accounting for Sustainable Society), 2022)
The purpose of this research is to produce a model that can explain the influence of Intergovernmental Revenue, Capital Expenditure, Regional Wealth Level and Size of Regional Government on Regional Government Financial Performance. This research method uses descriptive and verification methods. The population of this study, namely the Budget and Balance Sheet Realization Reports for all districts in the Nusa Tenggara Islands for the 2016-2020 period, was obtained as many as 37 districts. The technique of determining the sample uses a saturated sample. The data analysis technique used is panel data regression analysis. The results showed that Intergovernmental Revenue, Capital Expenditures, Level of Regional Wealth and Size of Local Governments had a positive effect on the Financial Performance of Local Governments. Keywords: Regional Government Financial Performance, Intergovernmental Revenue, Capital Expenditure, Regional Wealth Level, Size of Regional Government